Framework for Analyzing the Influencing Factors on Battery Circulation Systems - Uhlig, Edith; Scheller, Christian; Kishita, Yusuke; Kononova, Nelli; Proff, Moritz; Spengler, Thomas S.; Mennenga, Mark (Procedia CIRP, 2025)
In times of rapid technological advancement and increasing environmental consciousness, the society needs to address the challenges of handling waste streams of previous technological generations while already adapting to new emerging technologies. This requires agile circulation systems (CS) which foster a circular economy (CE) and whose development considers new product and process technologies simultaneously. To understand the complex interactions within such CS, a framework is developed to visualize the interconnections of external influences on the developments of products, processes and business models as central elements of a CS. We follow a hybrid approach and combine an expert workshop with a literature review. The PESTLE analysis is used to understand diversified external factors, showing the high relevance of key factors for the design of effective CS, such as the market development, regulatory framework conditions and technological innovations. Exemplarily, the emerging technology of solid-state batteries is considered in more detail, showing new challenges, still lacking research and knowledge on how to create effective CS. The framework can serve as a basis to build qualitative and quantitative assessments and simulations to predict future developments of CS.